2007
DOI: 10.1094/pdis-91-7-0865
|View full text |Cite
|
Sign up to set email alerts
|

Development of PCR Assays for the Identification of Species and Pathotypes of Elsinoë Causing Scab on Citrus

Abstract: Two scab pathogens of citrus, Elsinoë fawcettii and E. australis, cause citrus scab and sweet orange scab, respectively, and pathotypes of each species have been described. The two species cannot be readily distinguished by morphological or cultural characteristics and can be distinguished only by host range and the sequence of the internal transcribed spacer (ITS) region. In this study, random amplified polymorphic DNA (RAPD) assays clearly distinguished E. fawcettii and E. australis, and the sweet orange and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
26
0
1

Year Published

2010
2010
2018
2018

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(27 citation statements)
references
References 8 publications
0
26
0
1
Order By: Relevance
“…The identification of fungal pathogens based on polymerase chain reaction (PCR) using species-specific primers is now widely used, especially for economically important plant pathogens such as quarantine listed fungi or those that are difficult to isolate or cause symptomless [6,7]. The internal transcribed spacer regions (ITS1 and ITS4) within the nuclear ribosomal gene clusters are particularly attractive loci for the design of PCR-based detection assays since they are readily accessible using universal primers [8] typically present in high copy number increasing PCR sensitivity and often exhibiting sufficient inter-specific sequence divergence for the designing of species-specific primers [9].…”
Section: Introductionmentioning
confidence: 99%
“…The identification of fungal pathogens based on polymerase chain reaction (PCR) using species-specific primers is now widely used, especially for economically important plant pathogens such as quarantine listed fungi or those that are difficult to isolate or cause symptomless [6,7]. The internal transcribed spacer regions (ITS1 and ITS4) within the nuclear ribosomal gene clusters are particularly attractive loci for the design of PCR-based detection assays since they are readily accessible using universal primers [8] typically present in high copy number increasing PCR sensitivity and often exhibiting sufficient inter-specific sequence divergence for the designing of species-specific primers [9].…”
Section: Introductionmentioning
confidence: 99%
“…Several authors (12,14) have reported using the technique of Whiteside (25) to produce conidia of Sphaceloma spp. ; however, we were not able to induce sporulation using this technique.…”
Section: Discussionmentioning
confidence: 99%
“…The species-specific primers of Hyun et al (12) were used to further characterize the isolates of Elsinoë from jojoba. Primers Eaut1 and 5 along with EaNat1 were utilized.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…It attacks a wide variety of citrus species and cultivars, resulting in scab disease on leaves, twigs, and fruits , Hyun et al 2007, Goes and Reis 2009.…”
Section: Introductionmentioning
confidence: 99%